2019
DOI: 10.1002/jgc4.1193
|View full text |Cite
|
Sign up to set email alerts
|

Demographic differences in the utilization of clinical and direct‐to‐consumer genetic testing

Abstract: Genetic testing has increased over the last decade due to growth in the number of clinical and direct‐to‐consumer (DTC) tests. However, there is uncertainty about how increased DTC genetic testing affects disparities. Between November 2017 and February 2018, a nationwide electronic survey on experiences with genetic testing was conducted among adult Kaiser Permanente members. Logistic regression was used to calculate adjusted odds ratios and 95% confidence intervals comparing receipt of clinical and DTC geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 51 publications
2
39
0
Order By: Relevance
“…(2017) study about why DTC GT customers seek genetic counseling. Although there were study limitations (e.g., small number of interview participants who were asked to reflect on DTC GT a few years prior), findings are consistent with the prior DTC GT studies cited above, and interviewees’ key demographics are similar to more recent studies (Carroll et al, 2019). The perspectives of our interview participants contribute to the limited literature on this topic.…”
Section: Participant (P#) Sex Age At Testing Participant Had Childrensupporting
confidence: 79%
“…(2017) study about why DTC GT customers seek genetic counseling. Although there were study limitations (e.g., small number of interview participants who were asked to reflect on DTC GT a few years prior), findings are consistent with the prior DTC GT studies cited above, and interviewees’ key demographics are similar to more recent studies (Carroll et al, 2019). The perspectives of our interview participants contribute to the limited literature on this topic.…”
Section: Participant (P#) Sex Age At Testing Participant Had Childrensupporting
confidence: 79%
“…As consumer genomic testing continues to evolve, and companies are offering more health-related tests, they move closer to providing tests that are on par with clinical laboratories (Feero & Wicklund, 2020 (Carroll et al, 2020;Feero & Wicklund, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As an ideal mediating service to various genetic advancements, genetic counseling services bridge emerging therapies and treatment guidelines to the lay public. Carroll et al (2019) in the workforce for almost three decades as gathered by the PSS, which remains the most widely and consistently distributed survey within the profession. The data show that while representation of Asian Americans/Pacific Islanders has steadily increased since 1994 that of Blacks/African Americans has remained stagnant at one% of the membership.…”
Section: Introductionmentioning
confidence: 99%
“…As an ideal mediating service to various genetic advancements, genetic counseling services bridge emerging therapies and treatment guidelines to the lay public. Carroll et al (2019) using a large dataset of Kaiser Permanente members found that racial and ethnic disparities persist in the use of clinical genetic services. Historical and current underrepresentation of certain populations stand to be exacerbated with new advancements in genetics.…”
Section: Introductionmentioning
confidence: 99%